2011
DOI: 10.1017/s0029665111002175
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of takeaway meals served by independent small outlets

Abstract: Eating out of the home is growing in popularity and about 22 % of Britons have been found to purchase foods from takeaway outlets at least once a week and 58 % a few times a month (1) . Foods prepared outside the home are generally considered to be high in energy, saturated and trans fatty acids, total fat and salt (2) . While previous studies have investigated the nutritional quality of food provided by fast food chains, there is still a lack of data regarding the nutrient composition of meals purchased from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Most menu items offered by popular independent takeaways were discretionary. Similar to our finding, Jaworowska et al examined 489 commonly consumed meals from small, independent takeaway establishments and found they contributed a large proportion of daily energy and salt intake [17,32,33]. Recently, Goffe et al also reported 79% of 149 takeaway food outlets available on the market-leading OFD platform in England, obtained a health rating score of 2 or less out of a maximum of 5 using a novel outlet-level health metric [34].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Most menu items offered by popular independent takeaways were discretionary. Similar to our finding, Jaworowska et al examined 489 commonly consumed meals from small, independent takeaway establishments and found they contributed a large proportion of daily energy and salt intake [17,32,33]. Recently, Goffe et al also reported 79% of 149 takeaway food outlets available on the market-leading OFD platform in England, obtained a health rating score of 2 or less out of a maximum of 5 using a novel outlet-level health metric [34].…”
Section: Discussionsupporting
confidence: 86%
“…A key strength of this study is the investigation of the largest sample size of complete menus from independent takeways. To our knowledge, only Partridge et al and Jaworowska et al have evaluated the nutritional quality of menu items from independent takeaways although were limited to popular menu items only [17,32]. We also employed a comprehensive classification system of 38 food and beverage categories before assigning menu items as discretionary or FFG.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no studies published to date have differentiated between consumption of fast foods and other types of takeaway meals, and the majority of previous studies have concentrated on foods from fast‐food chain restaurants or have investigated food prepared outside of the home without considering the source, i.e., fast‐food chain restaurants or independent takeaway outlets. However, recent work indicates there are significant differences in the nutrient composition of different types of takeaway meals (e.g., Indian, Chinese, English, pizzas, kebabs) as well as between takeaway meals and ready‐to‐eat meal options of a similar type . To date, only one study has examined the relationship between the frequency of consumption of specific types of meals eaten out of the home (i.e., burgers, pizzas, fried chicken, fried fish, Chinese food, and Mexican food) and the incidence of type 2 diabetes, but this study was limited to restaurant food only .…”
Section: Resultsmentioning
confidence: 99%
“…We have shown takeaway food to be energy dense ( 1 ) , high in fat ( 1 ) , saturated fat ( 2 ) , salt ( 3 ) and sugar ( 1 ) and that takeaway food can be reformulated to be healthier without decreasing consumer acceptability ( 4 ) . Frequent takeaway consumption has also been associated with increased cardio-metabolic risk ( 5 ) .…”
mentioning
confidence: 99%